The influence of students’ problem-solving understanding and results of students’ mathematics learning - Sinaga, Bornok; Sitorus, Jonni; Situmeang, Tiurmaida (Frontiers in Education, 2023)
Problem-solving is the ability to understand issues and steps that will affect students’ mathematics learning results. The research goals are: describing students’ problem-solving understanding and mathematics learning results; testing the influence of gender and grade level on students’ problem-solving understanding and mathematics learning results; and testing the influence of students’ problem-solving understanding on mathematics learning results. The population is all students in the fourth through sixth grades at 2 primary schools (263 respondents). The sample consists of 244 respondents, with female and male respondents of 123 and 121, and low- and high-grade students of 74 and 170, respectively. The researchers calculated and converted scores into values. Statistical tests were carried out by means of analysis of linear regression and the t-test. The Me of students' mathematics learning results and problem-solving understanding are 69.679 and 66.889. The female students’ problem-solving understanding Me is greater than male ones', but male students' mathematics learning results Me is greater than female ones. The low-grade students’ problem-solving understanding Me is greater than high-grade students, but high-grade students' mathematics learning results Me is greater than low-grade students. Gender has no influence on students' mathematics problem-solving understanding or learning results. The grade level has a significant influence on students’ problem-solving understanding but no significant influence on mathematics learning results. The students’ problem-solving understanding has a significant influence on mathematics learning results, with a p value of 0.000. The research findings and results have implications for and contribute to assisting students in processing information and building mathematical knowledge.